PYTHON DATA VISUALIZATION ESSENTILAS GUIDE - RAHMAN KALILUR (NEW DELHI BPB PUBLICATIONS INDIA, 2021)
The book "Python Data Visualization Essentials Guide" by Kalilur Rahman is a comprehensive resource for mastering data visualization using Python. It emphasizes the importance of data visualization as a critical skill for data analysts, scientists, and hobbyists to effectively explore and present data insights.
BTECH ALL COMPUTER BRANCHES
Keywords: PYTHON; COMPUTERS